Analisis Trend Masa Penyelesaian Tugas Akhir dan Indeks Prestasi Mahasiswa Jurusan Pendidikan MIPA pada Masa Pandemi Covid-19 - Dimas Permadi; Anggreini Anggreini; Marina Setyarini (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
The education sector is one of the sectors that has experienced a significant impact due to the Covid-19 pandemic. The purpose of this study was to describe the trend of completing the final project and the achievement index of PMIPA students during the Covid-19 pandemic. The population and samples used are all undergraduate study programs within the PMIPA Department that have produced graduates in the 2020/2021 odd semester period to the 2020/2021 even semester. The research method used in this research is descriptive research. The data collection technique used in this research is in the form of observation and documentation. The data analysis technique used is descriptive qualitative to describe the trend of completing the final project and the achievement index of PMIPA majors. The results of the study indicate that the trend of completion of the final project and the achievement index is quite good, with an average completion of the final project of 8.37 months and an average GPA of 3.37. The results of this study are expected to help PMIPA majors in evaluating the learning process and completing the final project.